Thymoquinone/β-N-acetylglucosaminidase, a novel plant-derived combination, inhibited quorum sensing signaling pathways and disrupted biofilm in Staphylococcus aureus - Ahmad, Adel Attia M.; El-Naenaeey, El-Sayed Y.; Aloufi, Abeer S.; Khalifa, Eman K.; Khamis, Tarek; Elmowalid, Gamal A.; El-Hamid, Marwa I. Abd (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundDisrupting Staphylococcus aureus S. aureusbiofilms is of utmost importance in the medical field. Identifying herbal compounds, especially those comprising enzymes, with antibacterial and biofilm-degrading properties offers a promising alternative to conventional biofilm inhibitors. The present study explored the novel effects of β-N-acetylglucosaminidase (NAGase), an enzyme derived from jack beans, in preventing biofilm formation and disrupting established biofilms. Furthermore, it investigated the potential effects of combining NAGase with thymoquinone (TQ) extracted from Nigella sativa seeds.MethodsS. aureus isolates with robust biofilm formation were selected using a quantitative microtiter plate method. The effect of TQ and/or NAGase on the growth and dispersion of existing biofilms was evaluated using a crystal violet staining assay in a microtiter plate. The study also investigated their impact on quorum sensing (QS) molecules (agrA, agrC, and sarA) and icaA, agr, and atl gene regulation using computational modeling and real-time PCR analysis, respectively.ResultsTreatment with NAGase (2.5 U/mL) and TQ [1× minimum inhibitory concentration (MIC)] significantly reduced existing biofilms in multidrug-resistant and strong biofilm-forming S. aureus isolates by 40.9%–65.6% and 30.9%–69.3%, respectively. Notably, combining TQ and NAGase led to a greater reduction of established biofilm (61.8%–73.8%) compared to the untreated controls. Computer simulations revealed that the TQ ligand was a potent inhibitor of QS molecules, binding tightly to agrA and sarA. Notably, NAGase, whether used alone or in conjunction with TQ, led to a decrease in the expression of the atl, icaA, and agr genes.ConclusionsThe combination of TQ and NAGase is a promising antibiofilm agent in S. aureus, offering several advantages over traditional options. It effectively targets both QS pathways and breaks down polysaccharide intercellular adhesins, in addition to exhibiting antibacterial properties to combat bacteria within existing biofilms. The presence of NAGase, a naturally occurring enzyme in cellular lysosomes, combined with the optimal pharmacokinetic properties of TQ, makes it a potential treatment for systemic and localized S. aureus infections.